2010
DOI: 10.2478/v10141-010-0026-9
|View full text |Cite
|
Sign up to set email alerts
|

The Football Fan Community as a Determinant Stakeholder in Value co-Creation

Abstract: The Football Fan Community as a Determinant Stakeholder in Value co-CreationFans are of central importance to sport service production. Their passion, excitement, and involvement plays a crucial role in event implementation and value creation. Due to the importance of fans as "co-producers" of the sport service, the hypothesis of this research is that a fan community is a salient stakeholder in the value co-creation process. This paper focuses on how a football fan community engages in manifold interaction wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 9 publications
0
20
0
6
Order By: Relevance
“…as Zagnoli and Radicchi (2010) observe, spectators at sport events often create a 'fan community' that becomes a salient stakeholder in a process of co-creating value. In the context of Olympic brand research, meanings linked to 'team spirit' (Caslavova and Petrackova, 2011;Majid et al, 2007) are shown to extend to ethical behaviors and the propeace messages of 'hope' that many choose to associate with the Olympic movement.…”
Section: Discussionmentioning
confidence: 99%
“…as Zagnoli and Radicchi (2010) observe, spectators at sport events often create a 'fan community' that becomes a salient stakeholder in a process of co-creating value. In the context of Olympic brand research, meanings linked to 'team spirit' (Caslavova and Petrackova, 2011;Majid et al, 2007) are shown to extend to ethical behaviors and the propeace messages of 'hope' that many choose to associate with the Olympic movement.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst recently have scholars turned their attention over how value is co-created across various context-specific service environments (Vargo and Lusch 2016;Uhrich, 2014;Zagnoli and Radicchi, 2010;Anker et al, 2015) including music (Chaney, 2012;) sports (Woratschek et al, 2014;Stieler et al, 2014;Stieler et al, 2015), and the fine arts (Crossland, ), research has fallen short of capturing the unique nature of Fan Fests and the role of fans on value co-creation in such 'third' places of sport consumption. Our paper takes up this challenge and explores the still evolving nature of the Fan Fest.…”
Section: Exploring Value Co-creation In Fan Fests: the Role Of Fansmentioning
confidence: 99%
“…A football supporter community engages with its team, the local context, and the network of local actors in multiple ways. Their passion, excitement, and involvement plays a crucial role in the production of cultural and economic values in and around the club; an intricate process of co-creation which is often overlooked by owners and investors who are keen to relocate (Zagnoli and Radicchi, 2013). The rational reasons for moving must therefore be carefully considered against a dominant desire to stay if football clubs wish to also remain socially sustainable.…”
Section: The Greening Of Football Architecturementioning
confidence: 99%